GE_GERICHTE A/4733/2006 vom 22. November 2007 - GE Cour de justice (2007)
; AI(ASSURANCE) ; INTERDICTION D'ENTRÉE ; DOMICILE ; INTENTION DE S'ÉTABLIR ; DOMICILE EN SUISSE ; DOMICILE CONNU ; RECONSIDÉRATION ; INEXACTITUDE MANIFESTE ; PRESCRIPTION ; PÉREMPTION ; DEMANDE DE PRESTATION D'ASSURANCE | LAI6; LPGA13; LAI48